Anaplasma ovis genetic diversity detected by major surface protein 1a and its prevalence in small ruminants - Aktas, Munir; Ozubek, Sezayi (Elsevier Science Bv, 2018)
Anaplasma ovis is a widely distributed tick-borne rickettsial pathogen of sheep, goats, and wild ruminants. The aims of this study were to assess the prevalence, associations of Anaplasma ovis in sheep and goats, as well as its genetic diversity based on analysis of the msp1a gene. A total of 416 DNA samples from sheep (n = 236) and goats (n = 180) from four provinces in southeastern Turkey were analyzed by PCR. The overall A. ovis prevalence was 18% (CI 14.4-22.1). The infection rates of A. ovis varied from 15.9% to 21.8% in sampled provinces, and they were not significantly different. There was no difference between Anaplasma ovis infection in sheep (20.3%, CI 15.4-26.0) and goats (15.0%, CI 10.1-21.1) or in infection rate of animals < 1 year (21.8%, CI 14.9-30.1) compared to > 1 year (16.4%, CI 12.4-21.2). A significant association between A. ovis infection and the presence of Rhipicephalus bursa and Rhipicephalus turanicus was observed (P < 0.05). Prevalence of A. ovis-positive animals was higher in animals showing co-infection with Babesia and Theileria compared to those not co-infected (P < 0.05). The msp1a amino acid repeats were identified and used for the characterization of A. ovis strains. Forty partial msp1a gene sequences containing the repeated sequences of A. ovis were obtained, and 14 previously undescribed tandem repeats with 33 to 43 amino acids were found. Thirteen A. ovis genotypes were identified based on the structure of msp1a tandem repeats. The majority of A. ovis isolates exhibited one msp1a tandem repeat, with a maximum of three. This study revealed the msp1a could be used as a marker for geno-typing A. ovis, and high genetic diversity of A. ovis were found in small ruminants in Turkey.
Keywords: Anaplasma ovis; Msp1 alpha; Sheep; Goats